2023
DOI: 10.3389/fpsyt.2023.1160772
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality to insomnia: Sleep reactivity, sleep effort, and sleep hygiene as mediators

Abstract: BackgroundInsomniacs are heterogenous group with very diverse personalities. We aimed to investigate the mediating role of sleep reactivity (SR), sleep hygiene (SH), and sleep effort (SE) in the relationship between Type D personality and insomnia.Materials and methodsWe conducted a cross-sectional survey among 474 participants. The survey comprised the sociodemographic data form, Insomnia Severity Index (ISI), D Type Personality Scale (DS-14), Ford Insomnia Response to Stress Test (FIRST), Glasgow Sleep Effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Whilst negative affect and social inhibition were independently related to insomnia symptoms, negative affect emerged to be the most prominent predictor of insomnia when accounting for shared variance. These outcomes are partially replicated amongst Turkish university students (Uygur et al, 2023) and Polish high‐school teachers (Domagalska et al, 2021) where increased reports of insomnia symptoms were observed in those being characterised as Type‐D individuals. Likewise, North American students meeting the diagnostic criteria for insomnia demonstrated increased negative affect and social avoidance compared with normal sleeping controls (Yuksel et al, 2022).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Whilst negative affect and social inhibition were independently related to insomnia symptoms, negative affect emerged to be the most prominent predictor of insomnia when accounting for shared variance. These outcomes are partially replicated amongst Turkish university students (Uygur et al, 2023) and Polish high‐school teachers (Domagalska et al, 2021) where increased reports of insomnia symptoms were observed in those being characterised as Type‐D individuals. Likewise, North American students meeting the diagnostic criteria for insomnia demonstrated increased negative affect and social avoidance compared with normal sleeping controls (Yuksel et al, 2022).…”
Section: Resultsmentioning
confidence: 88%
“…Most studies collected cross‐sectional data, with N = 10 employing a longitudinal design (Akram et al, 2015; Dørheim et al, 2016; Ellis et al, 2021; Husson et al, 2015; Jansson‐Fröjmark & Linton, 2007; Larsgård & Saksvik‐Lehouillier, 2017; Reeve et al, 2018; Singareddy et al, 2012; Sørengaard et al 2022; Trudel‐Fitzgerald et al, 2017). Moreover, N = 15 studies restricted sampling to students (Brand et al, 2015; Emert et al, 2017; Fabbri et al, 2022; Lauriola et al, 2019; Lukowski & Tsukerman, 2021; Ma et al, 2020; Polner et al, 2018; Zamani Sani et al, 2023; Schmidt et al, 2010, 2018; Scott et al, 2017; Shealy et al, 1980; Yuksel et al, 2022; Uygur et al, 2023). Most studies ( N = 44) sampled individuals experiencing symptoms of insomnia, whereas the remaining sampled individuals meeting the appropriate diagnostic criterion for insomnia at the time of data collection ( N = 32) and deployed questionnaires assessing insomnia‐symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep impacts cognition, academic achievements, and daily activities [8,16]. Thus, it is crucial to investigate sleep quality throughout adolescence [17].…”
Section: Introductionmentioning
confidence: 99%